A prospective and retrospective study on conservative management of hepatic and splenic injury following blunt abdominal trauma - Nair, Induchoodan Ponnamma Pillai Sukumaran; P. S., Rajesh (International Surgery Journal, 2020)
Background: worldwide road traffic accidents accounts as the leading cause of death of young people. For a very long time most of the intra-abdominal injuries following blunt abdominal trauma were managed operatively. Conservative management is becoming more acceptable and effective management option for blunt abdominal trauma during the last few decades. Methods: This study was conducted in Government Medical College, Kottayam during September 2007 to December 2008. All conservatively managed blunt abdominal trauma patients during the study period were included in the study. Results: Out of 22 patients, 4 patients failed conservative management. Success rate was 81%. Most commonly injured solid organ in the study group was liver (77%). Maximum cases were of age group 10 to 20 (31.81%) years. 81% of patients were males. Motor vehicle accident was the most common cause of trauma (77%). Mean stay in intensive care unit was 4.2 days and mean hospital stay was 15.7 days. Mean systolic blood pressure was 110 mmHg ranging from 70 to 130 mmHg. 50% of patients had moderate hemoperitoneum and non-had massive hemoperitoneum. Conclusions: Non operative management is safe and effective approach in blunt spleen and liver injuries. Non operative management should be treatment of choice for all hemodynamically stable patients with blunt liver and splenic trauma.